Motive Analysis of the Partai Solidaritas Indonesia (PSI) in Supporting the Empty Box in the 2020 Ngawi District Election - Nizah, Zachrotun; Hilman, Yusuf Adam (Utan Kayu Publishing, 2022)
One of the areas that has a single candidate against the empty box in the 2020 regional elections is Ngawi Regency, which in the election has the support of a political party, the Indonesian Solidarity Party (PSI). This research aims to find out what motives the Indonesian Solidarity Party has given its support to empty boxes. The method used in this study is qualitative descriptive method. The results of this study revealed that the motive of the Indonesian Solidarity Party supports empty boxes that is because of in order to motive and because motive. In order to motive is first, PSI wants to Â convey to the public through political socialization that choosing this empty box is valid and does not violate the law. Second, provide space and containers for the community supporting empty boxes. Third, with PSI supporting this empty box hopes that democracy in Ngawi district will come back to life. Fourth, PSI wants to provide political education to the community. While because motive of the support of DPD PSI Ngawi regency against this empty box is the existence of a Political Dynasty in Ngawi Regency that is controlled by two families, namely the Harsono and Kanang families for approximately 20 years. This support is also motivated by administrators and members who have supported empty boxes first before they enter into the board of DPD PSI Ngawi Regency period 2020-2024.